STUDY OF THE RELATIONSHIP OF STRUCTURES AND PROPERTIES OF APV ELEMENTS (Scientific journal of the Fergana State University, 2024)
This article analyzes theoretical concepts of the appearance of anomalous photovoltage (APV) in structurally inhomogeneous semiconductor films with anomalous photovoltaics based on the parameters of thin films directly obtained in experiments, and also discusses the geometric quantities characterizing the crystallite boundary, the surface state formed at the boundary of the collision of crystallization fronts.